1974
DOI: 10.1111/j.1469-7998.1974.tb03173.x
|View full text |Cite
|
Sign up to set email alerts
|

Species variations in the foetal growth rates of eutherian mammals

Abstract: While the larger cetaceans have the greatest known specific foetal growth rates (Huggett & Widdas, 1951), examination has shown that among land mammals of a particular Order, Sub‐order or even Genus, there may be marked variation in rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…Because embryos often experience a time lag ( t 0 ) in growth at the beginning of the development period, the power function sometimes appears as M = a ( t − t 0 ) b . The exponent b typically assumes a value close to 3 (Huggett & Widdas 1951; Frazer & Huggett 1974); that is, mass increases approximately as the cube of time. A diagnostic for the goodness of fit of the power function is ln(dln M /d t ) = ln b − ln( t − t 0 ), according to which the logarithm of the exponential growth rate decreases linearly with age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because embryos often experience a time lag ( t 0 ) in growth at the beginning of the development period, the power function sometimes appears as M = a ( t − t 0 ) b . The exponent b typically assumes a value close to 3 (Huggett & Widdas 1951; Frazer & Huggett 1974); that is, mass increases approximately as the cube of time. A diagnostic for the goodness of fit of the power function is ln(dln M /d t ) = ln b − ln( t − t 0 ), according to which the logarithm of the exponential growth rate decreases linearly with age.…”
Section: Introductionmentioning
confidence: 99%
“…Rate of development is a fundamental component of the life histories of organisms. Although postnatal growth rate of vertebrates has received considerable attention as a life-history parameter (Case 1978;Zullinger et al 1984;Starck & Ricklefs 1998a), relatively less information is available for the relatively inaccessible embryo period (Frazer & Huggett 1974;Ricklefs 1987Ricklefs , 2006. Development is closely connected to longevity, with respect to both correlations across evolutionary lineages (Promislow 1991;Ricklefs & Scheuerlein 2001;Metcalfe & Monaghan 2003;Ricklefs 2006;De Magalhaes, Costa & Church 2007) and environmental effects of early conditions on later life (Barker & Martyn 1992;Desai & Hales 1997;Jennings et al 1999;Osmond & Barker 2000;Metcalfe & Monaghan 2001;Schwartz & Morrison 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Size differences at birth presumably reflect either an underlying difference in foetal specific growth rate or gestation time. In fact, there is a consistent relationship between size at birth, foetal specific growth rates and gestation time among vertebrates (Huggett & Widdas, 1951;Frazer & Huggett, 1974;Frazer, 1977;Millar, 1977Millar, , 1981Calder, 1982). Foetal specific growth rates are remarkably constant among terrestrial mammal species within the same taxonomic order and, as a result, the length of the gestation period in large part determines neonate size: canid species with shorter gestation times generally have smaller neonates (Fig.…”
Section: Growth Gestation Time and Comparative Morphology Of Canidmentioning
confidence: 97%
“…Nutrient intake in newly-born mammals varies not only with the volume of milk, but also with its fat content, so that growth rates after birth vary from one species to another, just as much as the specific foetal growth rates do (see Frazer & Huggett, 1974). Recent figures for the rat (Rattus norvegicus) show that while growth before birth is by a linear daily increase in length or in cube root of foetal weight, after birth and through weaning there is an equally steady daily increase in actual weight of the young (Frazer, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…In the latter, it has been shown (Huggett & Widdas, 1951) that plotting the cube root of foetal weight against time gives a linear growth plot. There is initial slow growth related to the time when the yolksac placenta is active, but once the chorio-allantoic placenta is functional, the slope of the second line is markedly steeper . Frazer & Huggett (1974) showed that this specific foetal growth rate varies considerably between species, the bats and primitive primates having values ranging from as low as 0.01 or 0-02, while the sea-cows go as high as 0.2, with seals from 0.08 to 0.15 and the cetaceans as high as 0-58 for the blue whale.…”
Section: Introductionmentioning
confidence: 99%